2001
DOI: 10.1097/00005131-200103000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Conventional Open Reduction and Internal Fixation Versus Calcium Phosphate Cement Fixation of a Central Depressed Tibial Plateau Fracture

Abstract: This study suggests that the non-weight-bearing postoperative period may be significantly reduced without clinically significant articular collapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 20 publications
1
44
0
1
Order By: Relevance
“…In full agreement with our data, a study investigating the same fracture type found no significant displacement when applying a bone substitute with or without screws. However, the importance of the bone substitute could not be elucidated as a treatment with screws only was not performed [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In full agreement with our data, a study investigating the same fracture type found no significant displacement when applying a bone substitute with or without screws. However, the importance of the bone substitute could not be elucidated as a treatment with screws only was not performed [3].…”
Section: Discussionmentioning
confidence: 99%
“…Then they were cut at middiaphysis to a length of 20 cm measured from the tibial plateau. The diaphysis of the bones was embedded in bone cement (Palacos, Heraeus Kulzer) in five degree valgus angulation in a custom-made device [3].…”
Section: Specimenmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro biomechanical testing of CPC in tibial plateau fracture models has demonstrated that the cement provides an adequate buttress to the overlying articular surface. 11,12 CPC is an injectable paste with a crystalline structure similar to bone. CPC sets under endothermic conditions, is biocompatible, biodegradable, and osteoconductive.…”
mentioning
confidence: 99%